2019
DOI: 10.1128/msphere.00670-18
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of the Conserved Aspergillus nidulans Transcription Factor Mac1 and Its Functions in Response to Copper Starvation

Abstract: Copper is an essential cofactor of enzymes during a variety of biochemical processes. Therefore, Cu acquisition plays critical roles in cell survival and proliferation, especially during Cu starvation. Knowledge of the key motif(s) by which the low-Cu-responsive transcription factor Mac1 senses Cu is important for understanding how Cu uptake is controlled. Findings in this study demonstrated that the Cu fist motif, but not Cys-rich motifs, is essential for Mac1-mediated Cu uptake in Aspergillus. In addition, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Metal responsive transcription factors are able to sense the copper concentration within the cell and orchestrate a response by activating the copper import or copper detoxification, as required. These two regulatory paths are under the control of two separate transcription factors (Keller et al 2005) which were first discovered in S. cerevisiae as Mac1 and Ace1 (Balamurugan and Schaffner 2006), and later described in A. nidulans and A. fumigatus (Antsotegi-Uskola et al 2017;Cai et al 2019;Kusuya et al 2017;Wiemann et al 2017).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Metal responsive transcription factors are able to sense the copper concentration within the cell and orchestrate a response by activating the copper import or copper detoxification, as required. These two regulatory paths are under the control of two separate transcription factors (Keller et al 2005) which were first discovered in S. cerevisiae as Mac1 and Ace1 (Balamurugan and Schaffner 2006), and later described in A. nidulans and A. fumigatus (Antsotegi-Uskola et al 2017;Cai et al 2019;Kusuya et al 2017;Wiemann et al 2017).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
“…A Cterminal copper binding domain with two cysteine-rich motifs is responsible for copper sensing (Kusuya et al 2017). Sitedirected mutagenesis studies in A. fumigatus and A. nidulans have demonstrated that Cys residues of the N-terminal BCu fist^domain are essential for MacA DNA binding (Cai et al 2019). Under copper limitation, AfMacA binds copper response elements 5′-TGTGCTCA-3′ in the gene promoter regions and enables the transcription of the Ctr proteins for copper uptake (Park et al 2017).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
“…At later stages (right), the host limits Cu availability to C. albicans . Mac1p is activated and induces Cu import as has been shown for numerous fungi (Jungmann et al ., 1993; Gross et al ., 2000; Marvin et al ., 2004; Woodacre et al ., 2008; Kusuya et al ., 2017; Cai et al ., 2019). Additionally, C. albicans Mac1p represses SOD1 , and induces SOD3 and AOX2 to maintain ROS homeostasis in the cytosol and mitochondria, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…AnctrB is the top hit of the low affinity copper transporter ScCtr2, which encodes a vacuolar Cu transporter ( Liu et al, 2012 ; Qi et al, 2012 ). Cai et al, 2019 recently identified AN3209 and AN3813 as copper uptake proteins in A. nidulans , and AnMac1 as the TF controlling their expression. In this work, AN3209 and AN3813 were named AnCtrA2 and AnCtrC, respectively, claiming they were AfCtrA2 and AfCtrC homologs, but the protein sequence analysis results support a different interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been reported that in the absence of the Ctr proteins A. fumigatus fails to grow in infected tissues ( Cai et al, 2017 ), corroborating the importance of Ctr protein expression for virulence. While this research was ongoing Cai et al (2019) published a paper describing the components of the copper uptake system in A. nidulans . This paper was mainly focused on the TF Mac1 and the presence of two copper transporter proteins termed, AnCtrA2 and AnCtrC, was reported.…”
Section: Introductionmentioning
confidence: 99%